Rocky Mountain Geo-Conference 2014 : proceedings of the 2014 Rocky Mountain Geo-Conference, November 7, 2014, Lakewood, Colorado - Strickland, Jere; Wiltshire, Richard L.; Goss, Christoph M. (American Society of Civil Engineers, 2014)
This Publication contains 11 papers that address the complex geotechnical challenges in geologic hazards, nondestructive evaluation, geo-construction, and the ground itself. Topics include: seepage reduction on dams and levees; debris flow risk assessment; testing rockfall barrier systems; landslide hazard ranking and remediation; collapsing soils; ground classification system for excavations; and flooding impacts on Left Hand Creek. This Publication focuses on Colorado and the Rocky Mountain West's specific geotechnical practice and experience. It will be valuable to anyone in geotechnical engineering, especially those working in similar geologic settings. -- Provided by publisher.
Keywords: Engineering geology -- Colorado -- Congresses.; elektronické knihy; electronic books